Service Learning Bagi Komunitas Ibu Rumah Tangga dalam Pelafalan Surah Al-Fatihah Sesuai Makhorijul Huruf dengan Metode Ummi di Dusun Konang - Istiqomah, Istiqomah; Saputro , Budiyono; Parera, Nurita; Maghfiroh, Nuning; Ulumuddin, Ahmad Ichya’ (Academia Publication, 2024)
Al Qur’an is used as a guide to life for Muslims until the end of time. So that in order to understand the meaning, you need to learn how to pronounce the Al-Quran properly and correctly. Surah Al-Fatihah must be read in prayer. If it is not read, then the prayer lacks harmony. UIN Salatiga students want to improve their concerns about reciting Surah Al-Fatihah fluently by applying the Ummi method. The aim of this community service is to help the housewife community in correctly reciting Surah Al-Fatihah. The community service method used is service learning by testing its effectiveness. The data collection technique is using tests, while the data analysis technique is using the t test. The results of the quality of recitation of Surah Al-Fatihah after and before being given the Ummi method respectively got an average score of 59.46 & 109.00. The results of hypothesis testing using paired sample t-test obtained a sig value. (2-tailed) is 0.000 < 0.05, so H0 is rejected and Ha is accepted. Thus, Ummi's method is effective on the quality of the recitation of Surah Al-Fatihah among housewives in Konang village. The ummi method can be recommended for reciting other surahs.